MMP/TIMP balance is modulated in vitro by 15dPGJ2 in fetuses and placentas from diabetic rats - Pustovrh, María Carolina (2009)
Background: Maternal diabetes is associated with morphological placental abnormalities and foeto-placental impairments. These alterations are linked with a dysregulation of the activity of matrix metalloproteinases (MMPs). We investigated the action of 15deoxyD12,14 prostaglandin J2 (15dPGJ2), a natural ligand of the peroxisome proliferator activated receptor (PPAR) gamma, on MMP-2 and MMP-9 activities and tissue inhibitors of matrix metalloproteinases (TIMP) levels in foetuses and placentas from diabetic rats. Materials and methods: Diabetes was induced in rat neonates by a single streptozotocin administration (90 mg kg)1 s.c.). At 13Æ5 days of gestation, foetal and placental homogenates were prepared for the determination of PPARgamma levels (western blot) and 15dPGJ2 concentration (enzyme-immunoassay), whereas the in vitro effect of 15dPGJ2 (2 uM) was evaluated on placental and foetal MMPs and TIMP activities (zymography and reverse zymography), nitrate ⁄ nitrite concentrations (Griess method) and thiobarbituric acid reactive substances (TBARS). Results: PPARgamma was increased while 15dPGJ2 was decreased in placentas and foetuses from diabetic rats. 15dPGJ2 additions were able to reduce the high activities of MMP-2 and MMP-9 present in diabetic placental tissues. 15dPGJ2 additions reduced MMP-2 activity in control and diabetic foetuses. TIMP-3 levels were decreased in diabetic placentas and 15dPGJ2 was able to enhance them to control values. Nitrates ⁄ nitrites and TBARS, metabolites of MMPs activators, were increased in the diabetic placenta and reduced by 15dPGJ2. Conclusions: This study demonstrates that 15dPGJ2 is a potent modulator of the balance between MMP activities and TIMP levels, which is needed in the correct formation and function of the placenta and foetal organs.